Catalysis of organic reactions through non-covalent interactions - Melnyk, Nika (Trinity College Dublin. School of Chemistry. Discipline of Chemistry, 2026)
This thesis presents a computational investigation into halogen bonding (XB) as a foundation for organocatalyst design, positioning it as both an alternative and a complement to traditional hydrogen-bond (HB) catalysis. While often compared to HB, XB interactions display unique characteristics, most notably a high degree of directionality, tunability, and mechanistic versatility, and the ability to promote different activation modes, making them a unique platform for catalyst development. The work is structured around successive chapters, beginning with a systematic computational study of symmetric monovalent XB scaffolds. By analysing the relationship between scaffold geometry, electronic structure, and donor accessibility, this part reveals how subtle variations in orientation and flexibility can dramatically alter substrate activation. It also demonstrates that XB catalysis is not limited to a single mechanistic pathway but can operate through multiple, context-dependent activation modes. Building on these principles, the thesis explores hypervalent XB architectures, where enforced rigidity and geometric control fundamentally reshape activation preferences. These donors emerge not as extensions of monovalent scaffolds, but as a distinct and powerful class of XB-based catalysts. The final chapter of the thesis examines the influence of counterions and intramolecular interactions, showing that counterions can actively stabilise specific key conformations and modulate $\sigma$-hole accessibility, thereby exerting a direct influence on catalytic behaviour. Together, these findings establish a comprehensive framework for computational design of XB-based organocatalysts, outlining the principles of scaffold design, mechanistic diversity, and environmental effects that define their reactivity and potential in asymmetric synthesis.
APPROVED
Keywords: Halogen Bonds; Non-covalent Interactions; Catalysis; Organocatalysis; DFT; Computational Chemistry